Building a Global Ecosystem Research Infrastructure to Address Global Grand Challenges for Macrosystem Ecology. Issue 5 (5th May 2022) - Loescher, Henry W.; Vargas, Rodrigo; Mirtl, Michael; Morris, Beryl; Pauw, Johan; Yu, Xiubo; Kutsch, Werner; Mabee, Paula; Tang, Jianwu; Ruddell, Benjamin L.; Pulsifer, Peter; Bäck, Jaana; et al.
Abstract: The development of several large‐, "continental"‐scale ecosystem research infrastructures over recent decades has provided a unique opportunity in the history of ecological science. The Global Ecosystem Research Infrastructure (GERI) is an integrated network of analogous, but independent, site‐based ecosystem research infrastructures (ERI) dedicated to better understand the function and change of indicator ecosystems across global biomes. Bringing together these ERIs, harmonizing their respective data and reducing uncertainties enables broader cross‐continental ecological research. It will also enhance the research community capabilities to address current and anticipate future global scale ecological challenges. Moreover, increasing the international capabilities of these ERIs goes beyond their original design intent, and is an unexpected added value of these large national investments. Here, we identify specific global grand challenge areas and research trends to advance the ecological frontiers across continents that can be addressed through the federation of these cross‐continental‐scale ERIs. Plain Language Summary: The development of several large‐, "continental"‐scale ecosystem research infrastructures over recent decades has provided a unique opportunity in the history of ecological science. By bringing together these research infrastructures and harmonizing their respective data will more broadly enable cross‐continental ecological research. It will also improve the capabilities of the research community to anticipate and address future global scale ecological challenges to the planet. Moreover, increasing the international capabilities of these research infrastructures goes beyond their original design intent, and is an unexpected added value of these large national investments. Here, we identify specific global grand challenge areas and research trends to advance the ecological frontiers across continents that can be addressed through the federation of these cross‐continental‐scale ecosystem research infrastructures. Key Points: For the first time in history, we are able to bring together continental‐scale Ecosystem Research Infrastructures globally This effort enables macrosystem ecologists to ask research questions from continent‐to‐continent in ways not available before This effort provides baseline data to tackle current and future unknown ecological challenges that society will face